Calculating the shear strength of a rock mass joint surface considering cyclic shear deterioration - Hu, Guangzhong; Wang, Lijuan; Bai, Jun; Ma, Song; Tang, Yao (Frontiers in Earth Science, 2022)
The dynamic response of rock mass is largely restricted by its joint surface. Previous studies have shown that the degradation of joint surface can not be ignored when calculating the shear strength of structural plane under cyclic load. Although several studies have attempted to calculate the cyclic shear strength of a rock mass joint surface, an established and reliable method for calculating the cyclic shear strength of rock mass discontinuities is still lacking, thus necessitating further research. In this study, the deterioration effect of the shear strength of the joint surface under cyclic shearing was first analysed using cyclic shearing tests. The influence of vibration degradation in rock mass on the structural surface, undulant angle equation of the joint surface, and calculation method for the basic friction angle under a cyclic shearing load are proposed. Furthermore, the calculation method for the shear strength of the structural surface under the action of cyclic shearing is established. The proposed method is further validated through case analysis. The influence of the cutting and filling (produced during the shearing process) on the shear strength of the joint surface cannot be disregarded. The improved model proposed in this study is in good agreement with the experimental results; however, when the improved proposed method is used to estimate the cyclic shear strength of the joint surface where the normal stress is too large, calculation results may contain certain errors.